2022
DOI: 10.3390/microorganisms10071337
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Vitamin B12 between Bacteria and Microalgae Does Not Systematically Occur: Case Study of the Haptophyte Tisochrysis lutea

Abstract: Haptophyte microalgae are key contributors to microbial communities in many environments. It has been proposed recently that members of this group would be virtually all dependent on vitamin B12 (cobalamin), an enzymatic cofactor produced only by some bacteria and archaea. Here, we examined the processes of vitamin B12 acquisition by haptophytes. We tested whether co-cultivating the model species Tisochrysis lutea with B12-producing bacteria in vitamin-deprived conditions would allow the microalga to overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…Diatoms have been shown to strongly induce vitB12-binding proteins under limiting growth conditions (Bertrand et al 2012) and modeling predicts active vitB12 release from bacteria in co-cultures (Grant et al 2014). How vitB12 is harvested from bacteria by microbial eukaryotes is not clear but directed release and lysis have both been suggested (Grant et al 2014; Nef et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms have been shown to strongly induce vitB12-binding proteins under limiting growth conditions (Bertrand et al 2012) and modeling predicts active vitB12 release from bacteria in co-cultures (Grant et al 2014). How vitB12 is harvested from bacteria by microbial eukaryotes is not clear but directed release and lysis have both been suggested (Grant et al 2014; Nef et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this cofactor may act as a common bacterial currency for mutualism with algae in exchange for algal fixed C, and it may play a key role in microbial community structure and function [ 48 ]. Nevertheless, not all B 12 -producing bacteria and algal B 12 auxotrophs establish mutualistic relationships, indicating a species-specificity that may be due to the amount of B 12 released or the type of C fixed secreted by the alga [ 49 , 50 ]. While some studies have shown that bacterial growth was required to support algal B 12 auxotrophs [ 51 ], others have reported that bacterial cell lysis was sufficient for that purpose [ 49 ].…”
Section: Chlamydomonas’ Bacterial Partnersmentioning
confidence: 99%
“…Nevertheless, not all B 12 -producing bacteria and algal B 12 auxotrophs establish mutualistic relationships, indicating a species-specificity that may be due to the amount of B 12 released or the type of C fixed secreted by the alga [ 49 , 50 ]. While some studies have shown that bacterial growth was required to support algal B 12 auxotrophs [ 51 ], others have reported that bacterial cell lysis was sufficient for that purpose [ 49 ]. In algae, the enzyme methionine synthase ( METH ) uses vitamin B 12 as a cofactor, but some algae, such as Chlamydomonas , also have a B 12 -independent isoform ( METE ) that allows them to grow without the vitamin, albeit less efficiently [ 52 ].…”
Section: Chlamydomonas’ Bacterial Partnersmentioning
confidence: 99%
“…Therefore, this cofactor may act as a common bacterial currency for mutualism with algae in exchange for algal fixed C, and play a key role in microbial community structure and function [48]. Nevertheless, not all B12-producing bacteria and algal B12 auxotrophs establish mutualistic relationships, indicating a species-specificity that may be due to the amount of B12 released or the type of C fixed secreted by the alga [49,50]. While some studies have shown that bacterial growth is required to support algal B12 auxotrophs, others have reported that bacterial cell lysis is enough for that purpose [49,51].…”
Section: Vitamin B12 Productionmentioning
confidence: 99%
“…Nevertheless, not all B12-producing bacteria and algal B12 auxotrophs establish mutualistic relationships, indicating a species-specificity that may be due to the amount of B12 released or the type of C fixed secreted by the alga [49,50]. While some studies have shown that bacterial growth is required to support algal B12 auxotrophs, others have reported that bacterial cell lysis is enough for that purpose [49,51]. In algae, the enzyme methionine synthase (METH) uses vitamin B12 as a cofactor, but some algae, like Chlamydomonas, also have a B12-independent isoform (METE) that allows them to grow without the vitamin, albeit less efficiently [52].…”
Section: Vitamin B12 Productionmentioning
confidence: 99%